COMPREHENSIVE PREVENTION AND MANAGEMENT OF DEGENERATIVE DISEASE CONTROL STRATEGIES: STRATEGI PENCEGAHAN DAN PENGELOLAAN PENYAKIT DEGENERATIF SECARA KOMPREHENSIF - Harianto, Susilo; Sulpat, Emuliana; Muhalla, Hafna Ilmy; Twistiandayani, Retno; Nasir, Abd; Supriati, Lilik; Rahmadi, Cucuk; Rindayati, Rindayati (Darmabakti Cendekia: Journal of Community Service and Engagements, 2025)
Background: Degenerative diseases develop as organ function declines due to the natural aging process. The prevalence of these diseases reaches approximately 65.7%, with a significant increase observed in heart disease and stroke cases. Objective: This community service program aimed to increase public understanding of degenerative disease control through comprehensive prevention and management strategies. Method: The activity was conducted through educational sessions consisting of lectures, discussions, and question-and-answer segments. To assess participants’ understanding, a pre-test and post-test were administered, each comprising ten questions with a maximum score of ten per question. The average score was calculated to measure improvement. In addition, health checks were performed, including body weight, height, blood pressure, waist circumference, blood sugar, uric acid, and cholesterol measurements as part of early detection and control efforts. Results: There was a noticeable increase in knowledge regarding the prevention and management of degenerative diseases based on 74 participants’ post-test. Health screening results 11 participants have overweight, 15 particpants have hypertension, 5 participants have pre-diabetic, 7 participants have hypercholesterolemia, and 6 participants have hyperuricemia. Meanwhile, 5 participants were found to be underweight. Conclusion: Education on the control of degenerative diseases has a positive impact on maintaining public health. Preventive efforts remain essential to achieving a better quality of life.